(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
In this article discusses the role of the effective usage of innovative technologies in teaching the languages. The internet links, which are effectively used during the lessons, innovative methods of teaching literature on distance learning at the present stage education. While learning a foreign language, effective innovative technologies help students to become more independent and increase their enthusiasm for language learning. Innovative technologies used effectively in the process of teaching language explored in this article.